PERBEDAAN PENGGUNAAN PASTA GIGI YANG MENGANDUNG XYLITOL DAN BAKING SODA UNTUK MENURUNKAN SKOR PLAK PADA SISWA SMPN 6 BANJARBARU - Aulia Puteri Shiddiek; Naning K Utami (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2018)
TITLETHE DIFFERENCE BETWEEN TOOTHPASTE USING XYLITOL AND BAKING SODA TO DECREASE PLAQUE SCORE STUDENTS IN SMPN 6 BANJARBARUABSTRACTDental and oral diseases are a world problem that can affect general health and quality of life. Based on preliminary study conducted by examining the plaque score of 10 students of SMPN 6 Banjabaru obtained the results of 4 students have plaque scores average 3.6 with bad category, 4 students have average plaque score 2,6 with medium category, and 2 students had an average plaque score of 1.3 with good category.This study aims to determine differences in the use of toothpastes containing xylitol and baking soda to decrease plaque score in students SMPN 6 Banjarbaru. The research used is quasi experimental (quasi experiment) with pretest-posttest design. The population of the study were 284 people and sampling with total sampling technique which amounted to 90 people.The result of the research showed that T independent sample T-Test, sig (2-tailed) p = 0,000 is smaller than α = 0,05 (p α), meaning Ho is rejected and Ha accepted.It can be concluded that there are differences in the use of toothpastes containing xylitol and baking soda to decrease plaque score on students of SMPN 6 Banjarbaru.It is recommended for students to use xylitol-containing toothpaste because the results show that xylitol toothpaste is better at reducing plaque score.